(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research aims to: Develop the skills of understanding the Quranic text among students of the College of the Great Imam University, by preparing a program based on syntactic guidance.To achieve the goal of the research, the researcher undertook the following procedures: • A theoretical study of what came with previous research, studies and literature related to the current research topic. • Preparing a list of the skills of understanding the Qur’anic text necessary for students of the Department of Call and Rhetoric. • Preparing a test for the skills of understanding the Qur’an’s for students of the Department of Call and Rhetoric. • Preparing the program based on syntactic guidance to develop the skills of understanding the Quranic text among students of the Department of Call and Rhetoric. • Selecting the sample of the research number (40) from the Department of Propaganda and Publications, and distributing it into two groups: experimental (20) and control (20). • The application of the test of comprehension skills of the Qur’anic text to the experimental and control groups as a pretest. • The application of the syntactic-based program to the experimental group students, while the control group is taught by using the traditional program test. • Conducting statistical treatment of the degrees of pre and post application, and a number of results were reached. The most important of which are: The effectiveness of the program based on syntactic guidance in developing the skills of understanding the Quranic text among students in the Department of Call and Rhetoric.